2010
DOI: 10.1016/j.jns.2010.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in stepping response time are associated with impairments in balance and mobility in people with Huntington disease

Abstract: Huntington disease (HD) is a disorder characterized by chorea, dystonia, bradykinesia, cognitive decline and psychiatric comorbidities. Balance and gait impairments, as well as falls, are common manifestations of the disease. The importance of compensatory rapid stepping to maintain equilibrium in older adults is established, yet little is known of the role of stepping response times (SRTs) in balance control in people with HD. SRTs and commonly-used clinical measures of balance and mobility were evaluated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…While this result is consistent with reports of reduced strength in the lower limbs of HD patients [22], the observed force deficit did not generalize to the STS test where the amount of force (reported here as rising index) was comparable for both groups. The contrast in force production by HD patients for the two tasks may reflect the use of different muscle synergies that are adaptively regulated to match different functional tasks [23,24].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…While this result is consistent with reports of reduced strength in the lower limbs of HD patients [22], the observed force deficit did not generalize to the STS test where the amount of force (reported here as rising index) was comparable for both groups. The contrast in force production by HD patients for the two tasks may reflect the use of different muscle synergies that are adaptively regulated to match different functional tasks [23,24].…”
Section: Discussionsupporting
confidence: 84%
“…These values represent relative increases in movement time of 60%, 53% and 70%, which are comparable to percent increases reported other syndromes in which the CNS is compromised such as fetal alcohol syndrome [20] and Parkinson's disease [21]. Delays of this magnitude in symptomatic HD patients result in impaired balance and mobility [10] and have possible significance for clinicians who design rehabilitation therapies for this clinical group. When performing the ST test, bradykinesia contributed most to the observed deficit in the HD patients and clinicians should target this parameter to maximize improved motor performance.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…When the COG falls outside the LOS area, neither hip nor ankle strategies will restore the balance and additional stepping strategies may be necessary to restore the balance or avoid falls. Studies have shown a strong correlation between the stepping capabilities and balance in older adults [16,17] and lack of stepping response is associated with impairments of balance, mobility, and motor performance in Huntington's disease [18], which is a progressive neurodegenerative disorder affecting the extrapyramidal system. Information on stepping response in PSP is not available.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the cases, the task is to simply press or release a button or a pedal in a few cm range of the finger or feet [16][17][18]. The instrument form [16] called American Educational (Hubbard Scientific 6027) Reaction Timer is shown in Fig.…”
Section: Reaction Time Testers From the Literaturementioning
confidence: 99%